Salud mental en estudiantes universitarios: análisis secundario de diálogos Socráticos y pensamiento crítico (2020)
From the initial approaches of Dr. Nora Londoño on the prevalence of symptoms of anxiety and depression in university students, 23 Socratic dialogues were carried out, where students made descriptions of the problems they were experiencing, by means of questions that they themselves constructed and answered. An analysis of these Socratic dialogues was carried out, seeking to describe the protective and risk factors and how these affect academic performance and / or dropout. The population of this project were young people between 17 and 29 years old belonging to the University of San Buenaventura Medellín and the CES. Various problems, conditions and characteristics were found that refer to the personal, social, family and economic dimensión. It was possible to identify that the students reported some risk behaviors or personality traits that, in addition to being explicitly and directly associated with their mental health, were manifested in various symptoms such as excessive worry, anxiety about academic exposures, mood Depressive, generalized fears and doubts that led individuals to question vocational orientation and, in addition, also directly or indirectly impacted the academic dimension, reducing motivation levels, leading to excessive procrastination, indifference, isolation, absenteeism and finally , to desertion